Searching for gold in a haystack: The reality of a visually impaired student in a higher education in Malaysia - Mohamad, Mariam; Muniandy, Balakrishnan (2014)
This study explores the extent of the life of a visually impaired student in a higher education setting in Malaysia.It concentrates to identify the needs that might have been overlooked.The research design of this study is qualitative and based on a single case study methodology.Data collection methods include interviews with the visually impaired student as well as observation during lectures and examinations.The study found out that there is a need for higher education to make some changes in the institutional system so that it would be moredisable friendly.It is important to provide assistive technologies such as embosser and screen reader as well as a human reader to support visually impaired learners in learning activities.In addition, there is also a need to improvise the examination system, where the type of questions need to be reviewed so that it would be more suitable for the visually impaired student.The library also needs to add resources that are suitable for visually impaired students such as audio books and e-books.Lecturers also need to be more aware about the needs of these students.Moreover, it would be helpful if the campus area is equipped with a track block to enhance mobility.The study is important to help stakeholders in higher education Malaysia to understand the needs of visually impaired learner in supporting them as a member in higher education.This is in accordance with the vision and philosophy of higher educations in Malaysia in providing education for all.